Dye-sensitized nanoparticles for heterogeneous photocatalysis: Cases studies with TiO2, ZnO, fullerene and graphene for water purification. (December 2018) - Youssef, Zahraa; Colombeau, Ludovic; Yesmurzayeva, Nurlykyz; Baros, Francis; Vanderesse, Régis; Hamieh, Tayssir; Toufaily, Joumana; Frochot, Céline; Roques-Carmes, Thibault; Acherar, Samir
Abstract: In this review, the use of dye-sensitized nanoparticles (NPs) for heterogeneous photocatalysis related to water purification is considered. The dye-sensitization by the mean of organic photosensitizers (PSs) appears as a relevant alternative method to enhance the photocatalytic efficiency and, particularly, to extend the activity towards visible light domain. The discussion covers the impact of several parameters on the photodegradation performances of various pollutants. Those factors include the type of NPs, the nature and the content of the PS, the linkage mode between the PS and the surface of the NPs (physisorption, covalent grafting), the presence of a heavy-metal atom coordinated to the ring of the PS, and the type of light used for the activation (UV, visible or solar). These processes have been conducted principally with TiO2 coupled with porphyrin or phthalocyanine. The main trends in terms of the effect of the PS nature, the linkage mode, the PS content, the nature of metallic heavy atoms are extracted by studying the photodegradation performance of the PS/TiO2 materials. In the research of alternative photocatalysts, PS/ZnO systems has been evaluated since ZnO shares many similarities with titania. Recent hybrid photocatalysts based on carbon materials such as PS/fullerene and PS/graphene are also discussed. For each system and under each irradiation source, the mechanism of the light-induced charge transfer and the nature of the radicals generated is also thoroughly described. When necessary, besides water treatment, other applications of the same photocatalysts are considered to illustrate some phenomena and mechanisms such as charge transfer and radicals nature. Highlights: Dye-sensitized NPs extend photocatalysis activity towards solar and visible light. Porphyrin/TiO2 and phthalocyanine/TiO2 most widely employed systems. PS/ZnO and PS/TiO2 similar photodegradation performances. PS/C60 : electron-donor acceptor system. GR utilized as electron mediators in dye-sensitized systems.